INNOVATIVE AND EFFECTIVE DEVELOPMENT OF OIL AND GAS INDUSTRY ENTERPRISES - Gafurov. Sh. N. (Modern American Journals, 2025)
This article outlines the organizational structure of oil and gas companies, one of the leading industries of the Republic of Uzbekistan and considered a driver industry for the development of our economy, the analysis of enterprises within this network, internal and external factors affecting effective development, and guidelines, phases, and directions for improving their activities in the near future.
Keywords: Effective development, conditions of effective management, effective management principles, the influence of innovation, financial situation, financing of projects, source of financing, oil and gas enterprises, effective management styles, general management structure.